Condition assessment of the structural elements of a reinforced concrete structure using non-destructive techniques. Issue 1 (April 2021) - Gupta, Nakul; Gupta, Ankur
Abstract: Assessment of the strength and durability properties of structural elements of a reinforced concrete structure can be of great importance for either tracing potential damaged areas or for carrying out the reliability analysis. Composite materials, these days have become an integral part of any construction. Most of the structures are built using concrete as the construction material. Inspite of the strong and durable nature of the concrete as a material, the RCC structures still face common structural issues that includes cracking, spalling, rusting of reinforcement, dampness, acid attack, carbonation etc. If these issues are left unattended during the initial stages then they may cause serious distress in the structures. This paper reports the condition assessment of the structural elements of a residential building using non-destructive techniques. The hardness and the strength of the cover concrete has been assessed using rebound hammer test, structural integrity and homogeneity by ultrasonic pulse velocity test, Additionally, carbonation test and resistivity test were also conducted to assess the extent of corrosion. The results of the assessment have shown a noteworthy decay in the strength and the durability properties of the structural elements.